Prophylactic and therapeutic efficacies of dietary zerumbone supplementation on the pathogenesis of atherosclerosis in cholesterol-fed rabbits - Hassan, Hemn Hassan Othman (2014)
Owing to the high incidence of cholesterol-induced cardiovascular disease particularly atherosclerosis. Furthermore, difficulty in finding a relatively efficacious, non toxic, readily available and cheap naturally existing antihyperlipidaemic and antiatherogenic complementary medicine warrant the search for such an agent. On the other hand, concerning the dangerous side effects of the chemical remedies utilized as a lipid lowering agents, therefore the current study was designed to investigate the prophylactic and therapeutic efficacies of dietary zerumbone (ZER) supplementation on the formation and development of atherosclerosis in rabbits fed with high cholesterol diet. A total of 72 New Zealand white rabbits (NZW) were divided randomly on two experimental studies carried out eight weeks apart. First experiment was designed to investigate the prophylactic efficacy of ZER in preventing early developed atheromas lesion. A total of 30 healthy rabbits were equally allotted in to five groups comprising of six animals each, namely control (CN), hypercholesterolemic diet (HCD) and ZER preventive groups (ZPI, ZPII and ZPIII). The second experimental trial is aimed at investigating the therapeutic effect of ZER in reducing the atherosclerotic lesion progression and establishment, wherein 42 healthy NZW rabbits were equally assigned to seven groups comprising of six animals each, namely control (CN), high-cholesterol diet (HCD), ZER treatment groups (ZI, ZII and ZIII), Simvastatin (SIM) group (SG) and zerumbone-simvastatin (ZER-SIM) combination group (ZSG). Rabbits in CN group were fed a standard rabbit chow, whereas those in the HCD, ZPI, ZPII, ZPIII, ZI, ZII, ZIII, SG and ZSG given a cholesterol-rich diet (1%) (1g cholesterol/100g pellet). However, rabbits in the ZPI, ZPII and ZPIII preventive groups given ZER at a dose of 8, 16 and 20 mg/kg respectively, two weeks prior to the onset of lipidemia induction and then with the course of cholesterol-rich diet as a prophylactic measure. On the other hand, those in the ZI, ZII and ZIII treatment groups were given ZER at a dose of 8, 16 and 20 mg/kg © COPYRIGHT UPM ii respectively, together with SIM at a dose of 15 and 5 mg/kg/day in SG and ZSG groups, respectively as a therapeutic measure. Rabbits were sacrificed and thoracic aortas simultaneously with the vital internal organs were collected at 10 weeks post cholesterol-feeding for the prophylactic trial and 14 weeks concerning the therapeutic trial. In regard to the second trial, rabbits received treatments for about four weeks after cessation of cholesterol-rich diet at 10th weeks. Following four weeks of supplementary treatment subsequent to high-cholesterol diet cessation at 10th week of 2nd experiment, ZER significantly reduce the serum lipid profile in all treated groups in a dose dependant manner as compared to non treated hypercholesterolemic animals. Sudanophilia, histopathological and ultrastructural changes show pronounced reduction in the plaque size in ZER medicated aortas. On the other hand, dietary supplementation of ZER for almost 10 weeks as a prophylactic measure indicates substantially decreasing in the lipid profile values and similarly plaque size in comparison with high-cholesterol non-supplemented rabbits. Furthermore, the results of oxidative stress and antioxidant biomarkers evaluation indicate that ZER is a potent antioxidant in suppression the generation of free radicals in term of atherosclerosis prevention and treatment. ZER significantly reduces the value of MDA and augments the value of SOD. Zerumbone significantly reduces the incidence of inflammatory response in the process of atherosclerosis formation and development through significant suppression of proinflammatory mediators NF-κB, iNOS and COX-2, in turn reduce the inflammatory cytokines secretion TNF-α, IL-6, IL-1, and IF-ᵞ evaluated by Western blotting and enzyme immunoassay techniques respectively. Conversely, reduction and suppression of inflammatory mediators will contribute to minimizing the chronic inflammatory cells mainly macrophages recruitment to the lesion and foam cell formation which is evident by immunohistochemistry and fluorescent assay of RAM-11. ZER significantly reduces the expression of RAM-11 in the intimal plaque in all ZER supplemented groups in a dose dependent manner. Moreover, ZER significantly reduces the proliferation and migration of vascular smooth muscle fibers through immunohistochemical and fluorescent detection of HHF-35 toward the intimal layer via induction of apoptosis, which is evident by down regulation of Bcl-2 and up regulation of Bax significantly evaluated by Western blotting technique. Furthermore, in vivo antiproliferative assay of ZER determined morphologically by TUNEL assay. In conclusion our data indicate that, dietary supplementation of ZER at doses of 8, 16 and 20 mg/kg alone as a prophylactic measure and as a supplementary treatment with simvastatin, significantly reduces early plague formation, development, and establishment via significant reduction in serum lipid profile together with suppression of oxidative damage, therefore alleviate atherosclerosis lesions. Simultaneously, ZER significantly suppresses inflammatory reaction within the plaque consequently prevent foam cell formation and plaque progression. Finally, ZER significantly lessens smooth muscle cells proliferation via induction of apoptosis eventually reduce the plaque size.